The role of borrowings importance in the modern German language of fashion (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article dwells upon the borrowings importance in the modern German language of fashion and some of them have been described. It has been determined that German fashion vocabulary is primarily based on foreign language vocabulary items (Gaelic and American English borrowings) and is still being increased due to various borrowings. The complex of French and American English borrowings in the modern German language represents certain culture level of contemporary German society
Keywords: borrowings; Gaelic borrowings; American English borrowings; the modern German language of fashion